Numerical simulations of particle behaviour in a realistic human airway model with varying inhalation patterns. (12th November 2019) - Kadota, Kazunori; Inoue, Nana; Matsunaga, Yoshihiro; Takemiya, Tetsushi; Kubo, Kenji; Imano, Hideki; Uchiyama, Hiromasa; Tozuka, Yuichi
Abstract: Objectives: For dry powder inhalers, the airflow properties in the airways could affect the deposition of inhaled particles; the flow patterns vary inherently between patients. This paper provides an evaluation of the effects of six airflow patterns on the behaviour of inhaled particles, as determined by using numerical simulations. Methods: Constant-velocity and unsteady inhalation flows were employed. The unsteady inhalation flow was set as an inhalation curve with a peak inspiratory flow rate. Under a constant flow of 28.3 l/min, the total flow rates were calculated to confirm the validity of the numerical simulation. The effects of different inhalation patterns on the particle behaviour in a realistic human airway model were revealed via numerical simulation. Key findings: Different flow rates affected the behaviour and deposition of the inhaled particles. Under an inhalation flow pattern, different airflow tendencies were observed between the right and left bronchi. Particle deposition in the airways was promoted by a vortex following terminal-velocity-like breath-holding. The inhalation flow pattern affected the behaviour and deposition of inhaled particles in the airway. Conclusions: Our results indicated that particle deposition in a realistic human airway model was promoted by a vortex formation following the terminal-velocity-like breath-holding. Moreover, the inhalation flow pattern significantly influenced the behaviour and deposition of inhaled particles in the airways. Additionally, the effect of flow patterns on the particle deposition in each airway position was quantitatively evaluated by numerical simulations for a realistic human airway model.